ANALISIS KOMPOSISI DAN STRUKTUR KOMUNITAS MAKROZOOBENTOS SEBAGAI BIOINDIKATOR KUALITAS PERAIRAN SUNGAI INDRAGIRI UNTUK RANCANGAN HANDOUT PADA PEMBELAJARAN BIOLOGI SMA - Dhea Oktama Rivaldo; Yuslim Fauziah; Suwondo Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Changes in the environment and human activity at this time is one of the causes of water pollution in various waters such as rivers, lakes, reservoirs and at sea. This study aims to determine the quality of the waters of the Indragiri River based on indicators of the macrozoobenthos community. The study was conducted in March - December 2019 along the Indragiri River in Kuantan Singingi Regency and was identified in the FKIP Biology laboratory of the University of Riau. Research results are integrated to design handouts. Determination of the research station by purposive random sampling by setting 5 stations and 3 random sampling times. Biological parameters observed were species composition, density, diversity index, species richness index, dominance index, and community similarity index. Physico-chemical parameters measured are temperature, pH, brightness, current strength, and DO. Data were analyzed descriptively. Based on the analysis, there were 6 types of macrozoobenthos composition. Based on the composition of the type of quality of the Indragiri River classified as moderate to severe. Based on the diversity index of macrozoobenthos, the quality of the waters of the Indragiri River is classified as heavily polluted to very heavy and the measurement results of the physical physics factors of the Indragiri River waters are classified as mild to severe. The results of research on the quality of the waters of the Indragiri River are used as material for the design of material handouts for environmental changes, specifically water pollution.Key Word : Macrozoobenthos, Physic-Chemical Water Factor River Water Quality.